2018
DOI: 10.1007/s00464-017-6011-1
|View full text |Cite
|
Sign up to set email alerts
|

15-year experience of laparoscopic single anastomosis (mini-)gastric bypass: comparison with other bariatric procedures

Abstract: LSAGB is an effective procedure for treating morbid obesity and metabolic disorders, which results in sustained weight loss and a high resolution of comorbidities.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
34
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(40 citation statements)
references
References 28 publications
4
34
2
Order By: Relevance
“…Generally, weight loss with OAGB seems to be better than that seen with either RYGB or SG [2,[5][6] but the difference in weight loss between OAGB and RYGB is small and perhaps clinically not meaningful. It should also be noted that marginally superior weight loss seen with OAGB in comparison with RYGB [7] might be due to higher rates of malnutrition [8][9] seen with it and that if surgeons used the recommended safe Bilio-Pancreatic Limb (BPL) length of 150 cm for OAGB [8,10], the superiority in weight loss might disappear or become clinically irrelevant.…”
Section: Comparative Efficacy Of Procedures For Weight Lossmentioning
confidence: 94%
See 1 more Smart Citation
“…Generally, weight loss with OAGB seems to be better than that seen with either RYGB or SG [2,[5][6] but the difference in weight loss between OAGB and RYGB is small and perhaps clinically not meaningful. It should also be noted that marginally superior weight loss seen with OAGB in comparison with RYGB [7] might be due to higher rates of malnutrition [8][9] seen with it and that if surgeons used the recommended safe Bilio-Pancreatic Limb (BPL) length of 150 cm for OAGB [8,10], the superiority in weight loss might disappear or become clinically irrelevant.…”
Section: Comparative Efficacy Of Procedures For Weight Lossmentioning
confidence: 94%
“…A recent study [26] found that at 5-year follow up SG was associated with a significantly lower rate of re-intervention compared to RYGB. Alkhalifah et al [6] found the revision rate to be lower (4.0%) with OAGB in comparison to RYGB (5.1%) or SG (5.2%). It is also worth noting here that a number of these revisions in this study, where authors used a tailored algorithm for BPL based on patients' BMI, were for malnutrition.…”
Section: Comparative Efficacy Of Procedures For Weight Lossmentioning
confidence: 97%
“…Due to a lack of an isolated biliopancreatic limb in MGB-OAGB, surgeons have theorized that patients would be more likely to experience intractable bile reflux as well as marginal ulcers. The reported revision rate ranged from 2 to 5% in patients undergoing MGB-OAGB [9][10][11]. In this study, we aimed to conduct a comprehensive literature review on the indications, operative techniques, and outcomes of revisional surgery following MGB-OAGB.…”
Section: Introductionmentioning
confidence: 99%
“…[ 2 3 ] It has many potential advantages such as technical ease, shorter operative time, lower complication rates, simpler revision and reversal, and lower incidence of internal herniation over Roux-en-Y gastric bypass (RYGB), the longest serving bariatric procedure. [ 4 5 6 7 ]…”
Section: Introductionmentioning
confidence: 99%
“…Regardless of these advantages, about 4% patients need revisional/reversal surgeries in the long-term after OAGB[ 5 ] due to protein-calorie malnutrition and/or excessive weight loss, persistent gastroesophageal reflux disease (GERD),[ 8 ] persistent marginal ulcer (MU), inadequate weight loss, or weight regain. Revisions for complications have been reported in about 1%–2% patients for GERD,[ 9 10 11 ] 0%–2% for MUs,[ 6 12 ] 0%–1.01% for severe malnutrition, and about 0.5% for incomplete weight loss and weight regain.…”
Section: Introductionmentioning
confidence: 99%